Water wave transmission and energy dissipation by a floating plate in the presence of overwash. (25th April 2020) - Nelli, Filippo; Bennetts, Luke G.; Skene, David M.; Toffoli, Alessandro
Abstract : Abstract : A numerical model, based on the two-phase incompressible Navier–Stokes equations, is used to study transmission of regular water waves by a thin floating plate in two dimensions. The model is shown to capture the phenomenon of waves overwashing the plate, and the generation of turbulent bores on the upper plate surface. It is validated against laboratory experimental measurements, in terms of the transmitted wave field and overwash depths, for a set of incident wave periods and steepness values. Corresponding simulations are performed for a thick plate that does not experience overwash, which are validated using experiments where an edge barrier prevents thin-plate overwash. The model accurately reproduces (i) the linear relationship between the transmitted and incident amplitudes for the thick plate, and (ii) the decrease in proportion of incident-wave transmission for the thin plate, as incident steepness increases. Model outputs are used to link the decreasing transmission to wave-energy dissipation in the overwash, particularly where bores collide, and in the surrounding water, particularly at the plate ends. It is shown that most energy dissipation occurs in the overwash for the shortest incident waves tested, and in the surrounding water for the longer incident waves. Further, evidence is given that overwash suppresses plate motions, and causes asymmetry in plate rotations.